Dihydrophenazine‐based double‐anchoring dye for dye‐sensitized solar cells. Issue 3 (3rd December 2019) - Kumar, Dhirendra; Chen, Yu‐Lin; Tsai, Chih‐Hung; Wong, Ken‐Tsung
Abstract: A novel dihydrophenazine‐based organic di‐anchoring dye DK‐11 was synthesized by utilizing a simple synthetic protocol. The dye was characterized by optical and electrochemical studies and used as a sensitizer for dye‐sensitized solar cell. The proposed butterfly structure was supported by IR experiments which ensured the binding of both carboxylic acid units on the semiconductor surface. Using the dye DK‐11, the device generated an efficiency of 5.07% with JSC, VOC, and FF values of 10.65 mA/cm 2, 0.67 V, and 0.71, respectively. Abstract : A new dihydrophenazine‐based dual‐anchoring dye was designed. The hypothesis of butterfly structure was manifested by IR experiment. Such structure is beneficial for the binding of both anchoring groups on TiO2 . The dye was employed as a sensitizer for DSSC and produced power‐conversion efficiency of 5.07% which is a decent performance among the reported thiophene‐free sensitizers.